The Role of Mass Media in Health Care Development: A Review Article (Journal of Advanced Research in Journalism & Mass Communication, 2018)
The role of mass media in the health development field is of high value. The strength of mass media can cause a major impact on a large population. The world is facing a lot of health issues and if the issues are not presented to the people then they can cause adverse effects to mankind. Mass media plays a vital role in presenting these issues to masses. This article reviews the research that is done on the role of mass media on health. The paper focuses on the surveys conducted in the published papers on mass media and health care development in the past and highlights the positive as well as negative aspects of media on the health of people. This article also discusses the ways to improve the performance of mass media in creating an impact on the health behavior of people. The conclusion of this article is the vital role played by mass media in health issues and health care. How to cite this article: Saraf RA, Balamurugan J. The Role of Mass Media in Health Care Development: A Review Article. J Adv Res Jour Mass Comm 2018; 5(1&2): 39-43. DOI: https://doi.org/10.24321/2395.3810.201807